The nature of spin excitations in the one-third magnetization plateau phase of Ba3CoSb2O9 - Y. Kamiya; L. Ge; Tao Hong; Y. Qiu; D. L. Quintero-Castro; Z. Lu; H. B. Cao; M. Matsuda; E. S. Choi; C. D. Batista; M. Mourigal; H. D. Zhou; et al. (Nature Communications, 2018)
Frustrated magnetic materials attract significant interest because their properties can become dominated by quantum fluctuations. Here the authors show that excitations in the plateau phase of a quantum magnet can be understood semiclassically even though the ground state involves strong quantum effects.